On the politics of the regulatory reform: econometric evidence from the OECD countries - Tomaso Duso (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
This paper empirically investigates contrasting views on the politics of economic policy. Merging different databases, we test various predictions coming form different strands of literature, with the aim of explaining the cross-sectional and temporal variation in the degree of regulatory intervention and entry liberalization in the digital mobile telecommunications industry of OECD countries during the 1990's. We analyze the role of political institutions, government's types and ideological position, industry and consumers' private interests, as well as the regulatory environment in shaping regulatory policy. We find strong evidence that all these sets of variables help to explain some degree of variability in the observed liberalization patterns among countries. Yet, political and regulatory institutions and the pressure of strong incumbent firms are found to be the most important factors. – – In diesem Beitrag werden verschiedene Theorieansätze zur Wettbewerbspolitik am Beispiel der Deregulierung der Mobilfunksindustrie in OECD-Ländern empirisch getestet. Die Rolle der politischen Institutionen, der Regierungstypologie und ihrer ideologischen Positionierung im politischen Spektrum, der privaten Interessen der Industrie und Konsumenten, sowie der Struktur von Regulierungsbehörden wird anhand einer neu entwickelten Datenbank untersucht, um die beobachte Variabilität in der Deregulierungspolitik zwischen OECD-Ländern zu erklären. Es wird gezeigt, dass alle diese verschiedene Faktoren die Deregulierung der Mobilfunksindustrie in OECDLänder während der 90er Jahren signifikant beeinflusst haben. Die Struktur der politische Institutionen und Regulierungsbehörden sowie der Druck starker Unternehmen im Markt sind jedoch die entscheidenden Faktoren des Deregulierungsprozesses.
Keywords: C23; D72; D78; L5; 330; Political Economy; Regulation; Entry Liberalization; Institutions; Ideology; Private Interests; Mobile Telecommunications; OECD